The effects of presentation methods and semantic information on multi-ethnicity face recognition - Kaarel Rundu; Kristjan Kask (European Journal of Psychology Applied to Legal Context, 2012)
Studies have shown that own-race faces are more accurately recognised than other-race faces. The present study examined the effects of own- and other-race face recognition when different ethnicity targets are presented to the participants together. Also the effect of semantic information on the recognition of different race faces was examined. The participants (N = 234) were presented with photos of own-race and other-race faces. For some participants the faces were presented with stereotypical names and for some not. As hypothesized, own-race faces were better recognised in target-present lineup and more correctly rejected in target-absent lineup than other-race faces. Concerning presentation method, both own-race and other-race faces were more correctly identified in target-present simultaneous than in target-present sequential lineups. No effects of stereotypical names on face recognition were found. The findings suggest that identifying multi-ethnicity perpetrators is a problematic and difficult task.